Postoperative MRI Findings Following Conventional and Extralevator Abdominoperineal Excision in Low Rectal Cancer - Oerskov, Kim Morgenstjerne; Bondeven, Peter; Laurberg, Søren; Hagemann-Madsen, Rikke H.; Christensen, Henrik Kidmose; Lauridsen, Henrik; Pedersen, Bodil Ginnerup (Frontiers in Surgery, 2021)
Aim: Disparity in outcomes for low rectal cancer may reflect differences in operative approach and quality. The extra-levator abdominoperineal excision (ELAPE) was developed to reduce margin involvement in low rectal cancers by widening the excision of the conventional abdominoperineal excision (c-APE) to include the posterior pelvic diaphragm. This study aimed to determine the prevalence and localization of inadvertent residual pelvic diaphragm on postoperative magnetic resonance imaging (MRI) after intended ELAPE and c-APE. Methods: A total of 147 patients treated with c-APE or ELAPE for rectal cancer were included. Postoperative MRI was performed on 51% of the cohort (n=75) and evaluated with regard to residual pelvic diaphragm by a radiologist trained in pelvic MRI. Patient records, histopathological reports and standardized photographs were assessed. Pathology and MRI findings were evaluated independently in a blinded fashion. Additionally, preoperative MRIs were evaluated for possible risk factors for margin involvement. Results: MRI-detected residual pelvic diaphragm was identified in 45 of 61 (75.4%) patients who underwent ELAPE and in 14 (100%) of 14 patients who underwent c-APE. An increased risk of margin involvement was observed in anteriorly oriented tumours with 16 of 73 (22%) anteriorly oriented tumours presenting with margin involvement vs. 7 of 74 (9%) non-anteriorly oriented tumours (p=0.038). Conclusion: Residual pelvic diaphragm following abdominoperineal excision can be depicted by postoperative MRI. Inadvertent RPD was commonly found in the series of patients treated with ELAPE-technique. Anterior tumour orientation was a risk factor for CRM involvement regardless of surgical approach.